2009
DOI: 10.1161/strokeaha.108.527366
|View full text |Cite
|
Sign up to set email alerts
|

May-Thurner Syndrome in Patients With Cryptogenic Stroke and Patent Foramen Ovale

Abstract: Background and Purpose We aimed to investigate the incidence of May-Thurner syndrome (MTS) in cryptogenic stroke patients with patent foramen ovale (PFO). Methods This was a retrospective study. All consecutive patients with cryptogenic stroke having undergone PFO closure from January 1st 2002 to December 31st 2007 at our institute were included in this study. Pelvic magnetic resonance venography (MRV) studies of all patients were reviewed to determine if features of MTS were present. Medical records and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 16 publications
1
31
0
3
Order By: Relevance
“…Although PFO is usually a left to right shunt, when it becomes a functional right to left shunt, emboli can pass from the venous system to the arterial system including cerebral arteries, thus ultimately leading to an ischemic event [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PFO is usually a left to right shunt, when it becomes a functional right to left shunt, emboli can pass from the venous system to the arterial system including cerebral arteries, thus ultimately leading to an ischemic event [8].…”
Section: Discussionmentioning
confidence: 99%
“…Kiernan, et. al (2009) found that 6.3% of cryptogenic stroke patients who had a PFO closure procedure demonstrated evidence of MTS on pelvic MRV [8]. However, this study reviewed radiology reports rather than MRV images and it did not compare the prevalence of MTS to normal control patients.…”
Section: Introductionmentioning
confidence: 99%
“…The coexistence of additional risk factors, such as pelvic venous clots, pelvic venous abnormalities (May-Thurner Syndrome), hypercoagulable state, smoking, or migraine with aura, may increase the risk associated with immobilization and decrease the travel time required to lead to a stroke. (Greer & Buonanno, 2001; Florez, 2003; Cramer, 2004; Ning, 2008; Kiernan, 2009; Ning, 2009) For example, May-Thurner Syndrome is a pelvic anatomic abnormality found in more than 6% of patients with PFO-related stroke, predisposing patients to excessive or pathological compression of the left common iliac vein by the right common iliac artery, thereby increasing pelvic venous congestion and stasis which may lead to thrombi formation. (Kiernan, 2009) Patients with multiple risk factors may potentially benefit from pre-flight DVT prophylaxis.…”
Section: Stroke and Pfomentioning
confidence: 99%
“…1 The article is innovative, being the first large-scale analysis of the association between May-Turner Syndrome, cryptogenic stroke, and patent foramen ovale (PFO). Nonetheless, it arises some uncertainties concerning the definition of "cryptogenic stroke".…”
Section: Cryptogenic Stroke: Cryptic Definition?mentioning
confidence: 99%
“…In the present study, cryptogenic stroke was defined as "a sudden focal neurological event in the absence of an identifiable cause such as uncontrolled hypertension, intracranial hemorrhage, ipsilateral carotid lesion, atrial fibrillation, intracardiac thrombus, degenerative neurological disorder or neoplasm." 1 In literature, the term cryptogenic stroke usually refers to strokes with no clearly definable cause even after extensive workup. 2 Approximately 30% to 40% of ischemic strokes are cryptogenic.…”
Section: Cryptogenic Stroke: Cryptic Definition?mentioning
confidence: 99%